MỘT SỐ KẾT QUẢ ÁP DỤNG PHƯƠNG PHÁP ĐỊA VẬT LÝ ĐÁNH GIÁ ĐẶC ĐIỂM PHÂN BỐ KARST TRONG VÙNG TAI BIẾN SỤT ĐẤT Ở HUYỆN THANH BA - PHÚ THỌ - Vũ, Trần Anh; Phòng, Lại Hợp; Ninh, Dương Thị; Thùy, Đặng Ngọc (Vietnam Journal of Earth Sciences, 2012)
Some results of geophysical application to assess the karst distribution in the region of landcollapse hazards in Thanh Ba - Phu Tho province The presence of land collapses in Thanh Ba, Phu Tho province is a type of geological hazards associated with karst activities that frequently occuring in many places in Vietnam. To understand their nature and mechanism, as well as determine the landcollapse potential areas for finding the measures of its mitigation, the measurable geological and geophysical investigations were conducted. The results of rational measurements by 2D electrical tomography and low frequency electromagnetic mapping using ERA equipment quickly provided informations about structural characteristics, karststic features and distribution in carbonate in surveyed areas. The methods are highly effective and can be applied to solve similar tasks elsewhere.